VDC_100102370104.0X000001. Issue 2 (February 2018) - Kalina, Michael; Ferraro, Joseph; Cohn, Stephen
A general surgeon shortage exists and fewer surgical residents specialize in trauma and surgical critical care (TSCC). We conducted a survey of trauma directors and administrators to determine what qualities are most desirable when hiring new TSCC fellowship graduates. Methods: The survey, entitled "A Survey of Directors of Trauma on Hiring New Attending Trauma Surgeons, " was submitted to the Eastern Association for the Surgery of Trauma (EAST) and distributed to the association members in January 2016. Categorical data were summarized using frequency counts and percentages. Comparisons of responses were analyzed using the chi-squared or Fisher's exact test. Statistical significance was denoted by P < 0.05. Results: A total of 317 respondents from 1364 submitted surveys presented a response rate of 23.2 per cent. Of these respondents, 85.8 per cent (n = 272) decide whether or not a new trauma surgeon is hired and 33.7 per cent were trauma directors. In all, 82.9 per cent work at academic centers and have an Accreditation Council for Graduate Medical Education–approved general surgery residency and 58.4 per cent have an Accreditation Council for Graduate Medical Education–approved surgical critical care or acute care surgery fellowship. In total, 72.6 per cent work in American College of Surgeons–verified trauma centers and 45.0 per cent hire new trauma surgeons as needed. Of the 272 respondents who decide whether or not a new trauma surgeon is hired, the recommendation of the residency and fellowship program director is important. Word of mouth was the most important manner of finding a new hire and the most important qualities of a new TSCC physician were personality and likeability. Conclusion: The survey revealed that well-trained, likeable, enthusiastic, and personable TSCC physicians are the best candidates for hire.